Justification of logistics concept in activities of building company - Крикавський, Віктор Євгенович (Technology audit and production reserves, 2016)
The basic conceptual foundations in building activity are proved based on the application of DuPont Model. It is established the need to introduce the logistics concept in supply as the most costly component of the building process. It is proved that the model of cost accounting based on time, TDABC allows optimizing not only the duration of operation realization but also the cost of its implementation. Ability to use TDABC model is proven for rationalization of ordering to optimize the operations of any sub-processes in the field of supply, improve cycle time of providing building services, eliminate redundant / useless waste of time and reduce logistics costs, such as stock maintenance costs, transport costs, stock depletion costs. It is established that the effective use of TDABC model can reach the trade up state with reduced costs and shortened time.